(untitled) (Agro Productividad, 2022)
Objective. To characterize the habitat of the Montezuma quail (Cyrtonyx montezumae) in Rancho Chapultepec, Durango, Mexico. Design/Methodology/Approach. From February to October 2020, fieldwork was carried out to search for Montezuma quail sites using transects and sounds. Subsequently each site-of-use was characterized; for each of them three random sites were located. Intercept lines (or Canfield), embedded frames, and nearest neighbour techniques were used. Recorded data were analysed using Principal component analysis (PCA); Frequency of observation (FO); Kruskal-Wallis; and Poisson regression (PR). Results. The PCA showed values for sites of use= 48, non-use= 43, and both= 36 of the present variability in vegetation-habitat variables. FO showed values per site of use = 6.25%; non-use = 2.08% and both = 1.56%; and per species in sites of use = 3.57, non- use = 3.85 and both = 3.33%. Kruskal-Wallis exhibited significant differences in richness and abundance and similarity in diversity. Poisson regression (PR) showed the effect of some vegetation-habitat variables on the Montezuma quail. Limitations /Implications of the study. The monitoring period evaluated only comprised a short space of time. It is suggested to extend the sampling time, allowing to visualize the population fluctuation regarding this variable. Findings/Conclusions: It was possible to determine that there is an association between the variables of the vegetation-habitat with the presence of C. montezumae. Vegetation type is the variable that determines the incidence of this species.